Economic Analysis of Renewable Energy Sources in European Union - STRIELKOWSKI, Wadim; LISIN, Evgeny (Journal of Environmental Management and Tourism, 2017)
Electrical power systems in the European Union are undergoing fundamental changes driven by environmental and energy security concerns that make energy generation and energy demand face a challenge of decarburization that is becoming a priority both in the EU and worldwide. Significant decarburization goes hand in hand with recent technological developments that put a strong emphasis on the electrification of the transport and heat demand sectors through the introduction of new technologies, such as electric vehicles (EV) and electric heat pumps (EHP).This paper tackles the economic and policy implications of the Renewable Energy Sources (RES) in the European Union (EU).The paper analyses the development of RES, their impact, as well as discusses their particular influence on the European electricity markets.